Staging value creation processes in short food supply chains of Italy - Marcello De Rosa; Chrysanthi Charatsari; Evagelos D. Lioutas; Yari Vecchio; Margherita Masi (Agricultural and Food Economics)
Abstract Farmers’ markets, as a short food supply chain system, are considered schemes that can contribute to local development, producing economic, environmental, and social value. These three facets of value can set the stage for building up the farmers' market value proposition. In the present study, we use the theoretical concept of the territorial staging system to identify farmers’ markets as sociotechnical contexts where producers and consumers interact to provide experiential resources and experiential engagement. This paper focused on the supply side of the proposed framework: by interviewing farmers markets’ directors and producers, an empirical analysis has been carried out with the purpose of identifying how these actors evaluate the three facets of value (economic, social, and environmental). The results show that, while directors emphasize economic value, farmers attribute higher importance to the environmental and, especially, social facet of value. These findings, which represent a primary research step that includes the consumers' contribution to the stage setting, highlight the diverging views of the actors involved. Results suggest that developing a stage that enhances consumer experience is a complex process and requires understanding different viewpoints.